1976
DOI: 10.1021/bi00648a012
|View full text |Cite
|
Sign up to set email alerts
|

The activation of ribulose-1,5-bisphosphate carboxylase by carbon dioxide and magnesium ions. Equilibria, kinetics, a suggested mechanism, and physiological implications

Abstract: Ribulose-1,5-bisphosphate carboxylase was activated by incubation with CO2 and Mg2++, and inactivated upon removal of CO2 and Mg2+ by gel filtration. The activation process involved CO2 rather than HCO3-. The activity of the enzyme was dependent upon the preincubation concentrations of CO2 and Mg2+ and upon the preincubation pH, indicating that activation involved the reversible formation of an equilibrium complex of enzyme-CO2-Mg. The initial rate of activation was linearly dependent upon the CO2 concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
369
1
3

Year Published

1980
1980
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 550 publications
(396 citation statements)
references
References 41 publications
23
369
1
3
Order By: Relevance
“…Reflective of the high affinity of activated Rubisco for CABP (Pierce et ai., 1980), formation of a stable, stoichiometric complex between the enzyme and the reaction-intermediate analogue is diagnostic of proper activation [carbamylation of active-site Lys 191 and binding of Mg2' (Lorimer et al, 1976;Lorimer, 1981;Donnelly et al, 1983)l. H287N and H287Q both form Mg2+-dependent complexes containing -1 molecule of CABP per active site, as reported previously for the H287N mutant (Lorimer et ai., 1987;Gutteridge et al, 1988).…”
Section: Enzyme Activatiodcabp Bindingmentioning
confidence: 99%
“…Reflective of the high affinity of activated Rubisco for CABP (Pierce et ai., 1980), formation of a stable, stoichiometric complex between the enzyme and the reaction-intermediate analogue is diagnostic of proper activation [carbamylation of active-site Lys 191 and binding of Mg2' (Lorimer et al, 1976;Lorimer, 1981;Donnelly et al, 1983)l. H287N and H287Q both form Mg2+-dependent complexes containing -1 molecule of CABP per active site, as reported previously for the H287N mutant (Lorimer et ai., 1987;Gutteridge et al, 1988).…”
Section: Enzyme Activatiodcabp Bindingmentioning
confidence: 99%
“…The K,,t(CO2) of rubisco activation in the reconstituted system was 4 micromolar C02, compared to a K,A,(C02) of 25 to 30 micromolar CO2 for the previously reported spontaneous CO2/Mg2' activation mechanism. The activation process characterized here explains the high degree of rubisco activation at the physiological concentrations of 10 micromolar CO2 and 2 to 4 millimolar RuBP found in intact leaves, conditions which lead to almost complete deactivation of rubisco in vitro.The photosynthetic assimilation ofCO2 is initiated by rubisco.2 This enzyme exhibits complex regulatory properties, including a requirement that it be converted to an activated state in order to acquire catalytic competency (8,9,14). The activation of rubisco in vitro occurs by the spontaneous addition of activating CO2 (ACO2) to the e-amino group of a lysine residue near the active site, followed by the addition of Mg2' (Eq.…”
mentioning
confidence: 99%
“…The enzyme may also act as an internal monooxygenase and catalyze the oxygenolysis of RuBP, leading to the production of glycolic acid during photorespiration (reviewed [ 11). For maximum catalytic rates, the enzyme must first be activated by preincubation with a divalent cation and CO2 [2,3] and there is some evidence to suggest that the CO2 activation site is distinct from the catalytic site [4,5]. With regard to the divalent cation requirement of the eucaryotic enzyme, it has been shown that Mn*', Ni*' and Co*+ will substitute for Mg*+ for both carboxylase [6] and oxygenase [7] activities.…”
Section: Introductionmentioning
confidence: 99%